OPPORTUNITIES TARGETOU THERAPY OF CHRONIC ENDOMETRITIS WITH PATAGONIA - Y. A. Petrov; V. E. Radzinsky; E. A. Kalinina; D. V. Shirokova; M. L. Polina (Медицинский вестник Юга России, 2015)
Purpose: assess the benefits of a differentiated approach in the treatment of chronic endometritis.Materials and methods: hysteroscopic visualization of macrotype HAE (hyperplastic, hypoplastic, and mixed) specific to each pathologic basis allows you to optimize the effectiveness diagnostic search of the disease.Results: comparison of immunoreactivity with HAE with variants of adaptive reactions showed characteristic for each macrotype the failure of the immune response.Conclusion: the dependence of variability in the response of the female body from different directional effects of rehabilitation therapy. Proven efficiency pathogenetic therapy in the amelioration of immunodeficiency or autoimmune reactions contributing to the chronicity of the inflammatory process in the endometrium.